EUROPROBE leadership (1991―2001) — V.I. Starostenko - R. Stephenson (Геофизический журнал, 2025)
This short paper is meant to be a brief 90th birthday celebration of Academician Vitaly Starostenko’s fundamental contributions to EUROPROBE (a solid Earth integrated multidisciplinary programme of the European Science Foundation in the 1990s). Several major workshops of EUROPROBE projects and themes were held in Ukraine under Vitaly’s leadership and guidance, not to mention innumerable visits of many, many scientists to Ukraine, especially to the Institute of Geophysics, enabling numerous collaborative scientific works and scientific publications. Two major geophysical acquisition programmes in Ukraine were developed and executed under the EURIPROBE umbrella.